Implementação no Brasil do artigo 12 da convenção sobre os direitos das pessoas com deficiência: os impactos da constitucionalização do direito à plena capacidade jurídica - Souza, Rafael Barreto (2013)
Convention on the Rights of Persons with Disabilities (CRPD) was introduced into the Brazilian legal system with a status equivalent to a constitutional amendment in 2008, under in article 5th paragraph 3rd of the Brazilian Constitution. The treaty involved the greatest civil society participation in the history of the United Nations, providing it with an unprecedented democratic legitimacy. The CRPD enshrines the right the full legal capacity to persons with disabilities in its article 12. It upholds the supremacy of autonomy, guarantees supported decision-making, and regulates rigorously any restrictions to legal capacity. The present dissertation aims at understanding what are the impacts of constitutionalizing the right to full legal capacity through the Convention in the Brazilian legal order. For this purpose, a study of the legislation, specialized academic literature, and reflections from the Critical Disability Studies, along with reports produced by the civil society and international organizations are investigated. In the research, first, the effects of incorporating international human rights treaties into the national order are examined. Next, conceptual models of disability, the current definition, as well as the history of its elaboration in view of civil society participation are analyzed. Also, a discussion concerning the effet utile on concrete cases is undertaken. Lastly, it is analyzed how the Convention alters the existing guardianship system and profoundly transforms the way to approach the legal capacity of persons with disabilities in Brazil.